Pengaruh Model Pembelajaran Berbasis Masalah dalam Strategi Penalaran Kausal berbasis Etnosains terhadap Hasil Belajar Fisika - Olis Sumalong; Amiruddin Kade; Muslimin Muslimin (Jurnal Kreatif Online, 2021)
This study aims to determine whether there was an effect of problem-based learning models in ethnoscience-based causal reasoning strategies on physics learning outcomes. The type of research used was an experimental research design with the equivalent pretest-posttest design. The sample was selected using purposive sampling technique and resulted in class XI IPA 1 as the experimental class and class XI IPA 2 as the control class. The instrument used is a test of learning outcomes in the form of multiple choice. Based on the results of data processing, the average posttest score of the control class students was 11.30 while the experimental class obtained the average posttest score was 15.30. Analysis of the test data was carried out using a two-party t-test statistical technique to test the difference in the mean scores of student learning outcomes with a significant level of =0.05. The results were tcount = 3.60 and ttable = 2.02. This means that the value of tcount was outside the H0 acceptance area. So it can be concluded that there was an effect of problem-based learning models in ethnoscience-based causal reasoning strategies on student physics learning outcomes.